Apetiolar Photosynthate Translocation - Choi, Ivan C. (1966)
Apetiolar transport of photosynthate (−14)C has been studied by feeding of (14)CO(2) to soybean petioles. Translocation occurs in the absence of leaves, but both the rate and velocity are diminished. The effect of root excision is not as profound as that of leaves. It appears, in some instances, to inhibit transport partially, so that accumulation of photosynthate develops, giving a steeper isotopic gradient. The effect of leaf darkening is to diminish its uptake of photosynthate from the petiole, possibly as a result of decreased transpiration in the lowered temperature of the darkened leaf. The data suggest that neither mass flow nor active transport provide an adequate basis for normal photosynthate transport but that the leaves provide a direct force requiring structural continuity, or a translocation carrier.